ANALISA HUKUM TERHADAP PERKAWINAN BEDA AGAMA (STUDI PENETAPAN NOMOR: 198/Pdt.P/2013/PN.Lmj) - Shelly Novita; Mardalena Hanifah; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
This research is motivated by the presence of PenetapanNomor : 198 / Pdt.P / 2013 / PN.Lmj State issued olehPengadilan Lumajang . In this determination , the judge mengabulkanpermohonan interfaith couples marriage between Sri Mulyani Christian with Muslim Hadi Susanto using legal basis terdapatdalamPasal 35 letters ( a) UndangNomor Act 23 of 2006 on Population Administration although basically according to Islam and Christianity not mengehendaki their interfaith marriage .Article 2 Paragraph 1 of the UndangNomor 1 1974 About Marriage mention that legal marriage is according to religion and beliefs of each and has been interpreted to mean that the law prohibits interfaith marriage . The author raised this issue with the formulation of the problem related to the basic consideration in determining the application judge interfaith marriage are associated denganUndang - Law No. 1 of 1974 About Marriage .The author uses the method of normative research on this issue , the approach used is an approach to literature and legislation . This serves to study the consistency is there kesesuaiandan antaradasar legal reasoning used by the judge UndangNomor Act 1 of 1974 TentangPerkawinandanjugaUndang - UndangDasar 1945 .From the research tersebutdapatdisimpulkan that the determination of the judge who granted the request of interfaith marriage in Determination No. 198 / Pdt.P / 2013 / PN.Lmj has violated the provisions of the marriage law judge judgment using a letter of Article 35 of Law No. 23 of 2006 About Administration Population that interfaith marriage is considered invalid . AGMA different marriage also violates the values contained in the Pancasila as the first principle states that " Belief in One Almighty " .Keywords : Marriage , Interfaith Marriage , Marriage Law